RELIABLE DISTRIBUTED SYSTEM FOR INITIALIZATION OF PSEUDORANDO NUMBER GENERATORS USING VIDEO DATA HASHING - DOBROVOLSKY, YURIY; PROKHOROV, PAVLO; PAVLIUCHENKO, OLEH; MAKARUK, OLEG (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Current article examines the advantages and methods of distributed systems development for pseudorandom variables (seeds) generation through external video recording and/or video shooting devices. An investigation is carried out on existing prototypes, specifically the LavaRand prototype, which is considered as a non-distributed version of the system that captures different states of a chaotic system from a group of stationary lava lamps, both the original implementation mentioned in the 1998 patent and a more advanced one are described. Also, implementation features are examined from the distributed systems theory point of view, in particular, along with node failures from a technical point of view, the concept of a logical failure is introduced, in which the results obtained from a node could be unsatisfactory, as well as the criteria for such a failure and the mechanisms for replacing such a node with another one. In addition, information is provided on the methods for converting frames into pseudorandom numbers, the problems of existing solutions are described, and additional arguments are given in favor of building a distributed system taking into account the specifics of the methods of generation from images. The rationale, advantages, and disadvantages of using a distributed system compared to a stationary approach are given. The implementation approaches in the context of the utilization of containerization and container orchestration technologies, are outlined. Issues related to the construction of a network of nodes and their general interaction are described, including the case when nodes could be split into groups of ability to capture, ability of seed ganaration and ability to perform both of operations on the same node. Thus, this article can be useful in implementing an additional and/or backup source of entropy using a distributed system of video sensors.